Pelatihan Pembuatan Telur Asin Herbal Pendukung Kebugaran Di Masa Pandemi Covid-19 Di Kelurahan Mataiwoi - Hafid, Harapin; Nuraini, Nuraini; Asminaya, Nur Santy; Aka, Rahim; Fitrianingsih, Fitrianingsih; S. Toba, Rachmita Dewi; Kimestri, Asma Bio (Vokasi Universitas Halu Oleo, 2020)
Covid 19 pandemic greatly threatens people's lives. Providing training to increase body immunity is done by educating the public to make herbal salted eggs. Through this training activity, PKK mothers are taught to choose materials, understand the causes and spread of Covid 19, and herbal salted egg processing. The results of the activity showed the enthusiasm and willingness of participants to implement making herbal products of the same type in their homes, some had business plans to make and market to the surrounding community. This training activity is needed by the community and can increase their knowledge and skills. The community hopes that this activity can continue periodically as a target of Halu Oleo University with various types of products.